High-alkali-resistant glass as well as preparation method and application thereof
By introducing high content of zirconia and TiO2 into the medicinal glass, a high alkali-resistant glass is formed, which solves the problem of corrosion of existing medicinal glass in a strong acid-base environment, and effectively packaging of the drug liquid with a pH greater than 12 is achieved, ensuring the safety and efficiency of the drug.
Patent Information
- Application Number
- CN202411412915.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-03-07
AI Technical Summary
Existing medicinal glasses are prone to corrosion in a highly acidic and alkaline environment and cannot effectively contain strong alkaline liquids with a pH greater than 12, resulting in problems such as tableting during the efficacy period of the drug, affecting the safety of the drug use.
A high alkali-resistant glass formula with high content of zirconium oxide (ZrO2) and TiO2 combined, including 64-67 wt% SiO2, 0.2-0.4 wt% Al2O3, 0.1-0.2 wt% TiO2, 14-18 wt% ZrO2, 16.7-18 wt% Na2O, 0.1-0.2 wt% K2O and 0.5-1 wt% Sb2O3, is used to form a glass with first-level alkali-resistant properties through a specific melting and annealing process.
The glass has high alkali resistance, with a corrosion rate of 7 to 14 mg/dm2, which can effectively resist the corrosion of NaOH solution with a ph greater than 12, avoid problems such as detoxification or quality of drug, and ensure the safety of drug use.
Smart Images

Figure CN119569331A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass, relates to pharmaceutical glass, and specifically relates to a high alkali-resistant glass and a preparation method and application thereof. Background Art
[0002] Glassware is a common container with a wide range of uses in the pharmaceutical field. Many drugs need to be contained in glassware. However, some acidic and alkaline drugs can easily corrode the container, affecting the quality of the drugs and causing the drugs to become ineffective. Especially for highly corrosive alkaline drugs, there is currently no suitable packaging material, which causes problems such as tablet peeling during the drug's shelf life, seriously affecting the safety of drug use.
[0003] Among traditional pharmaceutical glasses, low borosilicate glass is not resistant to corrosion by high-alkali media and cannot be used in environments with strong acidity and alkalinity. When the boron content is increased, due to its strong volatility, the volatilization of boron will cause a layer of white deteriorated glass to form on the glass surface, which in turn causes defects on the surface of the glass tube. Changes in the formulation of boron oxide, aluminum oxide, etc. change the surface tension of the glass. The surface tension determines the growth, melting and discharge speed of bubbles in the glass liquid, which in turn affects the roundness and wall thickness deviation of the glass tube. Due to Zr 4+ The high electricity price inhibits the precipitation of alkali metals. 4+ The enrichment on the glass surface will prevent the erosion of the glass by the alkaline solution. In order to effectively improve the alkali resistance of the glass, an appropriate amount of ZrO2 is introduced. However, the amount of ZrO2 introduced in current research is relatively small, and the alkali resistance achieved is limited, and it is unable to contain strong alkaline solutions with a pH greater than 12. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high alkali-resistant glass and a preparation method and application thereof, which has a first-class alkali resistance and can be used to contain strong alkaline liquid medicine.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A high alkali-resistant glass comprises raw materials including 64-67wt% SiO2, 0.2-0.4wt% Al2O3, 0.1-0.2wt% TiO2, 14-18wt% ZrO2, 16.7-18wt% Na2O, 0.1-0.2wt% K2O and 0.5-1wt% Sb2O3.
[0007] The present invention also protects a method for preparing the high alkali-resistant glass as described above, comprising the following steps:
[0008] Step 1: Weigh the raw materials according to the ratio and sieve them until they are fully mixed;
[0009] Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1400-1500° C., place it in a lifting furnace at 1550-1580° C. for 40-80 min, take out the crucible, and then pour the melt onto the mold;
[0010] Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 550-580°C for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
[0011] The present invention also protects a high alkali-resistant glass prepared by the above method and its application in containing strong alkaline liquid. The corrosion rate of the high alkali-resistant glass is 7-14 mg / dm 2 , achieving first-level alkali resistance.
[0012] Compared with the prior art, the present invention has the following technical effects:
[0013] The high alkali-resistant glass of the present invention adds a high content of zirconium oxide to the raw materials, and introduces TiO2 and ZrO2 to work together to improve the chemical stability; the signal corresponding to the Si-O-Zr bond in the infrared spectrum directly proves the strong bonding between the silicate network and Zr, and the insertion of Si-O-Zr into the silicate network indicates the strong connectivity between the Zr polyhedron and the silicate framework; the high content of ZrO2 is connected to the silicate network with a high degree of network connectivity, so the addition of zirconium oxide increases the degree of integrity and densification of the glass network. In addition, the solubility of zirconium oxide in alkaline solution is very small, which can significantly improve the alkali resistance of the glass; the corrosion rate of the high alkali-resistant glass prepared by the present invention is 7-14 mg / dm 2 The alkali resistance is level one, which is much lower than level one alkali resistance ≤75dg / dm 2 The glass has a small weight loss in NaOH solution with a pH value of >12, and can be used to contain strong alkaline liquid medicines, such as phenytoin sodium for injection and omeprazole for injection, etc. with a pH value of >11, to avoid problems such as flakes falling off or affecting the quality of liquid medicines due to poor alkali resistance.
[0014] The present invention uses quartz sand as a raw material to introduce SiO2, and uses alumina as a raw material to introduce Al2O3; SiO2, as a glass-forming oxide, plays a skeleton role in the glass structure; Al2O3, as an intermediate oxide, plays a role in reducing the tendency of glass crystallization and improving the chemical stability of glass; sodium carbonate and potassium carbonate are added to introduce sodium oxide and potassium oxide to reduce the melting temperature of glass liquid; Na2O is a network exosome, plays a role in breaking bonds and promoting melting, can provide O2, so that [A1O6] becomes [A1O4] and enters the glass network, and a high content of sodium oxide can reduce the glass The melting point of glass can be improved by adding sodium oxide, which can improve the problem of too high melting temperature caused by zirconium oxide, making it easier to melt. This characteristic makes sodium oxide a good flux, which helps to promote the formation of glass during high-temperature melting. By adding sodium oxide, the viscosity of glass can be reduced, the fluidity of glass can be increased, the glass performance can be improved, and the thermal expansion coefficient of glass can be increased. K2O can promote the melting of glass and reduce the crystallization effect of glass. The raw material does not contain B2O3, which avoids the degeneration of glass liquid caused by boron volatilization, which not only increases the consumption of raw materials and reduces the quality, but also corrodes the kiln and shortens the kiln life. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the density variation diagram of Example 1-5;
[0016] Figure 2 The weight loss change diagram of Examples 1-5 after being eroded by different media;
[0017] Figure 3 This is a scan of Example 1 subjected to alkali corrosion;
[0018] Figure 4 This is a scan of Example 5 subjected to alkali corrosion;
[0019] Figure 5 It is the FTIR infrared spectrum of Example 1-5. DETAILED DESCRIPTION
[0020] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0021] Example 1
[0022] A method for preparing highly alkali-resistant glass comprises the following steps:
[0023] Step 1, weighing raw materials according to 67wt% SiO2, 0.4wt% Al2O3, 0.2wt% TiO2, 14wt% ZrO2, 17.8wt% Na2O, 0.1wt% K2O and 0.5wt% Sb2O3 and sieving them until they are fully mixed to obtain a batch;
[0024] Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1450°C, place it in a lifting furnace and keep it at 1550°C for 40 minutes, then take out the crucible and pour the melt onto the mold;
[0025] Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 550°C for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
[0026] The alkali-resistant pharmaceutical glass prepared in this embodiment was tested, and the thermal expansion coefficient α of this embodiment was 50~300℃ =8.27×10 6 / ℃; expansion transition temperature is 596.9℃, expansion softening temperature is: 681.0℃; the density of the product tested by Archimedes method is 2.61g / cm 3 ; The water resistance loss was tested by weight method, and the maximum weight loss of glass was 16.33 mg / dm 2 ; Using DIN ISO 12116 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass in acid resistance test is 0.62mg / dm 2 ; Using DIN ISO 695 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass was 14.42 mg / dm 2 .
[0027] Example 2
[0028] A method for preparing highly alkali-resistant glass comprises the following steps:
[0029] Step 1, weighing raw materials according to 66wt% SiO2, 0.3wt% Al2O3, 0.1wt% TiO2, 15wt% ZrO2, 18wt% Na2O, 0.1wt% K2O and 0.5wt% Sb2O3 and sieving them until they are fully mixed to obtain a batch;
[0030] Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1450°C, place it in a lifting furnace and keep it at 1560°C for 50 minutes, then take out the crucible and pour the melt onto the mold;
[0031] Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 560° C. for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
[0032] The alkali-resistant pharmaceutical glass prepared in this embodiment was tested, and the thermal expansion coefficient α of this embodiment was 50~300℃ =8.21×10 -6 / ℃; expansion transition temperature is 610.4℃, expansion softening temperature is: 690.4℃. The density of the product tested by Archimedes method is 2.63g / cm 3 ; The water resistance loss was tested by weight method, and the maximum weight loss of glass was 8.16 mg / dm 2 ; Using DIN ISO 12116 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass in acid resistance test is 0.37mg / dm 2 ; Using DIN ISO 695 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass was 14.37 mg / dm 2 .
[0033] Example 3
[0034] A method for preparing highly alkali-resistant glass comprises the following steps:
[0035] Step 1, weighing raw materials according to 65wt% SiO2, 0.4wt% Al2O3, 0.15wt% TiO2, 16wt% ZrO2, 17.25wt% Na2O, 0.2wt% K2O and 1wt% Sb2O3 and sieving them until they are fully mixed to obtain a batch;
[0036] Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1450°C, place it in a lifting furnace and keep it at 1560°C for 60 minutes, then take out the crucible and pour the melt onto the mold;
[0037] Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 560° C. for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
[0038] The alkali-resistant pharmaceutical glass prepared in this embodiment was tested, and the thermal expansion coefficient α of this embodiment was 50~300℃ =7.94×10 -6 / ℃; expansion transition temperature is 617.5℃, expansion softening temperature is: 690.4℃. The density of the product tested by Archimedes method is 2.63g / cm 3 ; The water resistance loss was tested by weight method, and the maximum weight loss of glass was 8.12 mg / dm 2 ; Using DIN ISO 12116 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass in acid resistance test is 0.36mg / dm 2 ; Using DIN ISO 695 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass is 8.95 mg / dm 2 .
[0039] Example 4
[0040] A method for preparing highly alkali-resistant glass comprises the following steps:
[0041] Step 1, weighing raw materials according to 65wt% SiO2, 0.3wt% Al2O3, 0.2wt% TiO2, 17wt% ZrO2, 16.9wt% Na2O, 0.1wt% K2O and 0.5wt% Sb2O3 and sieving them until they are fully mixed to obtain a batch;
[0042] Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1400°C, place it in a lifting furnace and keep it at 1560°C for 60 minutes, then take out the crucible and pour the melt onto the mold;
[0043] Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 560° C. for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
[0044] The alkali-resistant pharmaceutical glass prepared in this embodiment was tested, and the thermal expansion coefficient α of this embodiment was 50~300℃ =8.30×10 -6 / ℃; expansion transition temperature is 621.2℃, expansion softening temperature is: 705.1℃. The density of the product tested by Archimedes method is 2.65g / cm 3 ; The water resistance loss was tested by weight method, and the maximum weight loss of glass was 10.72mg / dm 2 ; Using DIN ISO 12116 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass in acid resistance test is 0.33mg / dm 2 ; Using DIN ISO 695 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass was 8.74 mg / dm 2 .
[0045] Example 5
[0046] A method for preparing highly alkali-resistant glass comprises the following steps:
[0047] Step 1, weighing raw materials according to 64wt% SiO2, 0.2wt% Al2O3, 0.2wt% TiO2, 18wt% ZrO2, 16.7wt% Na2O, 0.2wt% K2O and 0.7wt% Sb2O3 and sieving them until they are fully mixed to obtain a batch;
[0048] Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1500°C, place it in a lifting furnace and keep it at 1580°C for 80 minutes, then take out the crucible and pour the melt onto the mold;
[0049] Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 580°C for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
[0050] The alkali-resistant pharmaceutical glass prepared in this embodiment was tested, and the thermal expansion coefficient α of this embodiment was 50~300℃ =8.65×10 -6 / ℃; expansion transition temperature is 631.9℃, expansion softening temperature is: 716.5℃. The density of the product tested by Archimedes method is 2.65g / cm 3 ; The water resistance loss was tested by weight method, and the maximum weight loss of glass was 17.48 mg / dm 2 ; Using DIN ISO 12116 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass in acid resistance test is 0.31 mg / dm 2 ; Using DIN ISO 695 standard, the maximum weight loss of the prepared alkali-resistant pharmaceutical glass was 7.61 mg / dm 2 .
[0051] Figure 1 It is the density variation diagram of Example 1-5; Figure 2 is a graph showing the weight loss changes of Examples 1-5 after being eroded by different media; Figure 2 It can be seen that the corrosion rate of the high alkali-resistant glass prepared in Examples 1-5 is 7-14 mg / dm 2 The alkali resistance is level one, which is much lower than level one alkali resistance ≤75mg / dm 2 The glass has a small weight loss in NaOH solution with a pH value greater than 12 and can be used to contain strong alkaline liquid medicine.
[0052] Figure 3 This is a scan of Example 1 subjected to alkali corrosion; Figure 4 is a scan of Example 5 subjected to alkali corrosion; Figure 3 and Figure 4 By comparison, it can be seen that with the increase of ZrO2, the delamination of the glass is significantly improved, that is, the alkali resistance is improved.
[0053] Figure 5 is the FTIR infrared spectra of Examples 1-5; Figure 5 Medium, 460cm -1 The peaks on the left and right are the symmetrical bending and stretching vibrations of the cyclic Si-O-Si bond; at 500 cm^ -1 With the increase of ZrO2, the absorption peak intensity increases. By comparing the characteristic peaks in the literature, it can be seen that the absorption peak intensity increases in the range of 500-600 cm^ -1 The range mainly involves the characteristic vibration of the zirconium-oxygen bond (Zr-O-Zr bond); 800cm -1The signal corresponding to the Si-O-Zr bond directly proves the strong bonding between the silicate network and Zr, which is inserted into the silicate network through Si-O-Zr, indicating the strong connectivity between the Zr polyhedron and the silicate framework; at 1 000 cm -1 It is mainly the vibration of Si-O-Si bonds, which indicates that the Si-O-Zr bonds break and transform into Si-O-Si bonds as the temperature increases.
[0054] The high alkali-resistant pharmaceutical glass prepared by the present invention can be widely used in acidic, alkaline, and water injection drugs with strict pH requirements when used as drug packaging. The high alkali-resistant pharmaceutical glass prepared by the method of the present invention has chemical stability, low density, and no flakes, and has considerable economic and social benefits and broad application prospects. Therefore, the preparation method of the present invention has a very broad application prospect.
[0055] The above are only preferred embodiments of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the present invention through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A high alkali-resistant glass, characterized in that: Ingredients include: 64-67wt% SiO2, 0.2-0.4wt% Al2O3, 0.1-0.2wt% TiO2, 14-18wt% ZrO2, 16.7-18wt% Na2O, 0.1-0.2wt% K2O and 0.5-1wt% Sb2O3.
2. A method for preparing high alkali-resistant glass as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Weigh the raw materials according to the ratio and sieve them until they are fully mixed; Step 2: directly add the mixed ingredients in step 1 into a platinum crucible preheated to 1400-1500° C., place it in a lifting furnace at 1550-1580° C. for 40-80 min, take out the crucible, and then pour the melt onto the mold; Step 3: After the melt is formed, it is quickly transferred to an annealing furnace, kept at 550-580°C for 30 minutes, and then cooled to room temperature along with the furnace to obtain a high alkali-resistant glass.
3. A high alkali-resistant glass prepared by the method according to claim 2, characterized in that: The corrosion rate is 7-14 mg / dm 2 .
4. Use of the high alkali-resistant glass as claimed in claim 3 in containing strong alkaline liquid medicine.
Citation Information
Cited By
Water-resistant strong-alkali-resistant high-zirconium low-aluminum glass as well as preparation method and application thereof
CN120553984A